Prolidase‐proline dehydrogenase/proline oxidase‐collagen biosynthesis axis as a potential interface of apoptosis/autophagy. (4th April 2016) - Zareba, Ilona; Palka, Jerzy
Abstract: Prolidase is a cytosolic imidodipeptidase that specifically splits imidodipeptides with C‐terminal proline or hydroxyproline. The enzyme plays an important role in the recycling of proline from imidodipeptides for resynthesis of collagen and other proline‐containing proteins. The mechanism of prolidase‐dependent regulation of collagen biosynthesis was found at both transcriptional and post‐transcriptional level. The increase in the enzyme activity is due to its phosphorylation on serine/threonine residues. Prolidase‐dependent transcriptional regulation of collagen biosynthesis was found at the level of NF‐κB, known inhibitor of type I collagen gene expression. Proline dehydrogenase/proline oxidase (PRODH/POX) is flavin‐dependent enzyme associated with the inner mitochondrial membrane. The enzyme catalyzes conversion of proline into Δ 1 ‐pyrroline‐5‐carboxylate (P5C), during which reactive oxygen species (ROS) are produced, inducing intrinsic and extrinsic apoptotic pathways. Alternatively, under low glucose stress, PRODH/POX activation produces ATP for energy supply and survival. Of special interest is that PRODH/POX gene is induced by P53 and peroxisome proliferator‐activated gamma receptor (PPARγ). Among down‐regulators of PRODH/POX is an oncogenic transcription factor c‐MYC and miR‐23b*. On the other hand, PRODH/POX suppresses HIF‐1α transcriptional activity, the MAPK pathway, cyclooxygenase‐2, epidermal growth factor receptor and Wnt/b‐catenin signaling. PRODH/POX expression is often down‐regulated in various tumors, limiting mitochondrial proline utilization to P5C. It is accompanied by increased cytoplasmic level of proline. Proline availability for PRODH/POX‐dependent ATP or ROS generation depends on activity of prolidase and utilization of proline in process of collagen biosynthesis. Therefore, Prolidase‐PRODH/POX‐Collagen Biosynthesis axis may represent potential interface that regulate apoptosis and survival. © 2016 BioFactors, 42(4):341–348, 2016